KETERATURANDANCARAMENGKONSUMSI TABLETFe DENGANKEJADIANANEMIAPADAIBUHAMIL - Juarna, Juarna (JURNAL MEDIA KESEHATAN, 2015)
Anemia is one of the factors underlying maternal mortality indirectly. In Indonesia, theincidence of anemia of pregnancy still quite high at 40%. High incidence of anemia in health centersBengkulu City West Rim of 30.30%. The purpose of this study was to determine the relationshipof order and how to consume iron tablet with anemia in pregnant women in the region ofBengkulu City Health Center West Rim. This research used descriptive analytical method withcross-cut approach, research was conducted in health centers West Rim Bengkulu City on July11 to August 11, 2012. With the population of the entire third trimester pregnant women who visitedthe clinic, pustu, BPS and conduct home visits totaled 35 pregnant women, sampling with atotal sampling and analysis using Chi square test. The result was that the vast majority (54.3%) ofpregnant women regularly consume iron tablet. Most (57.1%) of pregnant women consume irontablet right way. Almost half (37.1%) of pregnant women suffer from anemia. Chi square test resultsshowed no relationship between regularity consume iron tablet with anemia (p = 0.012).There was a relationship between how consume iron tablet with anemia (p = 0.005). Counselingneeded to be done by the officer to provide knowledge about the benefits of iron tablet to thepublic especially pregnant women to reduce the incidence of anemia.